AESTHETIC SURGERY: IMPACT ON QUALITY OF LIFE - Khan, Sikandar Ali; Ali, Ghazanfar; Rehman, Habib Ur; Tariq, Muhammad; Raza, Maqbool; Fareed, Ghulam (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the impact of aesthetic surgery on quality of life. Study Design: Cross-sectional study. Place and Duration of Study: The departments of Psychiatry, Plastic Surgery and ENT, Combined Military Hospital Multan, from Jan to Nov 2020. Methodology: Seventy-four patients were enrolled for this study. They underwent aesthetic surgery. A standard questioner was designed for these patients and response was obtained before undertaking the procedure and then after six months postoperatively. The questions were designed keeping in mind the specific type of surgery. Questions on Life Satisfaction, and the Patient Health Questionnaire (PHQ-4) were asked. The data were collected and analyzed by using SSPS-25. Results: There is high satisfaction postoperatively after aesthetic surgery. There are improvements in quality of life (p=0.03), physical well-being (Health) (p=0.03), body image (p=0.02), emotional stability (p<0.01) and emotional distress (Depression) (p=0.04 and anxiety (p=0.01) were noted to be reduced. Conclusion: Aesthetic surgery leads to higher satisfaction in physical appearance, health, emotional stability and reduction of anxiety.